Visual Thinking as a Predictor of Cognitive curiosity in Early Childhood Stage in Taif Governorate - Al-Ansari, Khawlah Jamil; Al-Juaid, Najlaa Attyah (Journal of Educational and Psychological Sciences, 2023)
This study aimed to reveal the level of visual thinking, cognitive curiosity level and the relationship between them. The study examined the ability of visual thinking to predict cognitive curiosity in the children in age of early childhood stage in Taif Governorate. To fulfill this aim, the researcher used the descriptive approach (correlational, comparative causal, predicative). The sample consists of 230 male and female children from early childhood in Taif Governorate, have applied visual thinking test developed by Abdultawab (2020) and cognitive curiosity scale developed by Thabet (2006). The study results conclude that there is a high level of visual thinking and cognitive curiosity in the study sample. There is significant statistical correlation between visual thinking and cognitive curiosity. There are no significance gender differences in visual thinking and its skills, and there are significant gender differences in cognitive curiosity with preference to females. In addition, the study has concluded that cognitive curiosity could be predicted through the visual thinking skills (link between the relationship in the picture, identify the picture and image analysis) at the study sample. In the light of these results, the researcher has provided a number of recommendations most important are as follows. Adding activities and experiences to the kindergarten curricula that arouse the motivation of cognitive curiosity and develop children's visual thinking, holding development courses to train teachers to plan educational experiences in ways that develop visual thinking.
Keywords: Visual Thinking; Cognitive Curiosity; Early Childhood Stage